2017
DOI: 10.1136/openhrt-2017-000591
|View full text |Cite
|
Sign up to set email alerts
|

Comparable effect of aliskiren or a diuretic added on an angiotensin II receptor blocker on augmentation index in hypertension: a multicentre, prospective, randomised study

Abstract: BackgroundThe effects of antihypertensive drug combination therapy on central blood pressure (BP) and augmentation index (AI) have not been fully elucidated. We investigated the effects of the direct renin inhibitor, aliskiren, or a diuretic added to an angiotensin II receptor blocker on AI in patients with essential hypertension.MethodsA 24-week, prospective, multicentre, randomised, open-label study enrolled 103 patients already treated with valsartan. Participants were randomly allocated to receive either v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…After having reviewed the title and abstract, 3,845 were excluded. Of the 162 full-text articles retrieved, 142 original articles were excluded for various reasons ( Figure 1 ), leaving 20 eligible original articles in the analysis ( Chen et al, 1995 ; Klingbeil et al, 2002 ; Ariff et al, 2006 ; Dart et al, 2007 ; Jiang et al, 2007 ; Schneider et al, 2008 ; Mackenzie et al, 2009 ; Matsui et al, 2009 ; Boutouyrie et al, 2010 ; Doi et al, 2010 ; Vitale et al, 2012 ; Kubota et al, 2013 ; Radchenko et al, 2013 ; Kim et al, 2014 ; Koumaras et al, 2014 ; Ghiadoni et al, 2017 ; Jekell et al, 2017 ; Miyoshi et al, 2017 ; Webster et al, 2017 ; Choi et al, 2018 ), comparing RAS inhibitors ( n = 21) or CCBs ( n = 6) with diuretics, β-blockers, or an α-blocker ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After having reviewed the title and abstract, 3,845 were excluded. Of the 162 full-text articles retrieved, 142 original articles were excluded for various reasons ( Figure 1 ), leaving 20 eligible original articles in the analysis ( Chen et al, 1995 ; Klingbeil et al, 2002 ; Ariff et al, 2006 ; Dart et al, 2007 ; Jiang et al, 2007 ; Schneider et al, 2008 ; Mackenzie et al, 2009 ; Matsui et al, 2009 ; Boutouyrie et al, 2010 ; Doi et al, 2010 ; Vitale et al, 2012 ; Kubota et al, 2013 ; Radchenko et al, 2013 ; Kim et al, 2014 ; Koumaras et al, 2014 ; Ghiadoni et al, 2017 ; Jekell et al, 2017 ; Miyoshi et al, 2017 ; Webster et al, 2017 ; Choi et al, 2018 ), comparing RAS inhibitors ( n = 21) or CCBs ( n = 6) with diuretics, β-blockers, or an α-blocker ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…CAVI may indicate the differential effects of various types of CCBs on arterial stiffness. Recent studies also report that novel antihypertensive agents, mineralocorticoid receptor blocker and direct renin inhibitor, also lower CAVI [51][52][53] .…”
Section: (E) Sleep Apnea Syndromementioning
confidence: 97%
“…Many studies have reported that CAVI is high in people with hypertension [ 56 , 57 ]. Calcium channel blockers [ 58 , 59 ] and renin-angiotensin-aldosterone system inhibitors, including angiotensin receptor blockers [60][61][62] , angiotensin-converting enzyme inhibitors [63] , mineralocorticoid receptor blockers [64] , and direct renin inhibitors [65] , can improve CAVI. The reduction in arterial stiffness in response to antihypertensive treatment can be related to blood pressure lowering, but additional blood pressure-independent effects may also be involved.…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%